If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.9(9x + 4) = 0.07 + -1(x + -3) Reorder the terms: 0.9(4 + 9x) = 0.07 + -1(x + -3) (4 * 0.9 + 9x * 0.9) = 0.07 + -1(x + -3) (3.6 + 8.1x) = 0.07 + -1(x + -3) Reorder the terms: 3.6 + 8.1x = 0.07 + -1(-3 + x) 3.6 + 8.1x = 0.07 + (-3 * -1 + x * -1) 3.6 + 8.1x = 0.07 + (3 + -1x) Combine like terms: 0.07 + 3 = 3.07 3.6 + 8.1x = 3.07 + -1x Solving 3.6 + 8.1x = 3.07 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 3.6 + 8.1x + x = 3.07 + -1x + x Combine like terms: 8.1x + x = 9.1x 3.6 + 9.1x = 3.07 + -1x + x Combine like terms: -1x + x = 0 3.6 + 9.1x = 3.07 + 0 3.6 + 9.1x = 3.07 Add '-3.6' to each side of the equation. 3.6 + -3.6 + 9.1x = 3.07 + -3.6 Combine like terms: 3.6 + -3.6 = 0.0 0.0 + 9.1x = 3.07 + -3.6 9.1x = 3.07 + -3.6 Combine like terms: 3.07 + -3.6 = -0.53 9.1x = -0.53 Divide each side by '9.1'. x = -0.05824175824 Simplifying x = -0.05824175824
| (0.046*281)/(281+x)=0.039 | | 7v+10=-2(v+4) | | y+5z=21 | | x/4-x/8+8=x+8 | | [2x-3]/3+2=[2-3x]/5 | | -5x+15=145 | | 9r-2(r+2)=5(3r-5)-35 | | 1/2y+6/2=-2 | | -2x-2*7=-6 | | 0.6(6x+7)=1.3-(x-3) | | 6z-6=8z-3z | | 5/x+15=50 | | -9(z+6)=-10 | | (0.046*281)/(281+65.7)=x | | 13x-(6x-5)=54 | | -x-4=28 | | 108-(6x+8)=6(x+8)+x | | h(t)=-14t^2+56t+9 | | ((11x)/3)-x | | 6r-5.1+3.5r=-1.1+9r | | r=67+6.21(188)+12.3(66)-6.2(25) | | 4y-8+y+55=8y+50-6y | | 5x+1=3x | | 1/9x+1/2x+2/9=59/18 | | (80x+52*5+5500)/(x)=144 | | 9u-39=6(u+3)-3 | | 8(x+1)=8x+3 | | -9+x+4x^2=0 | | 9u-39=6(u+3).3 | | -12+x+4x^2=0 | | (80*115+52*5+5500)/(115)=x | | 0.7x-4.5=0.4 |